Valley pseudospin relaxation of charged excitons in monolayer MoTe2. (13th October 2020) - Smoleński, T; Kazimierczuk, T; Goryca, M; Nogajewski, K; Potemski, M; Kossacki, P
Abstract: Zeeman effect induced by the magnetic field introduces a splitting between the two valleys at K + and K − points of the Brillouin zone in monolayer semiconducting transition metal dichalcogenides. In consequence, the photoluminescence signal exhibits a field dependent degree of circular polarization. We present a comprehensive study of this effect in the case of a trion in monolayer MoTe2, showing that although time integrated data allows us to deduce a g -factor of the trion state, such an analysis cannot be substantiated by the timescales revealed in the time-resolved experiments.